Investigating the Use of Waste Vehicle Tyres as Partial Replacement of Coarse Aggregates in Structural Concrete. - Nkwasibwe, Kraph (Kabale University, 2024)
Utilization of industrial waste products in concrete has attracted attention all around the world due to the rise of environmental consciousness. Worldwide, Waste-Tyre Rubber is one of the significant environmental problems. In this work, experiments were carried out by using recycled Rubber Tyres as a partial replacement for coarse aggregates. The mechanical properties of Rubberized Concrete were determined for the 7th day and 28th day and compared with the conventional concrete. The mix was designed of concrete class 20 in ratios 1:2:3 with a constant water-cement ratio of 0.59. The waste tyre rubbers of a maximum size of 20mm were used. The specimens were prepared by replacing coarse aggregate with 5, 10, 15, and 20% of the volume of Rubber aggregate. A total of 30 cube specimens were cast. The results of the test were compared with the respective conventional concrete properties. The strength of Rubberized Concrete decreased, among which 5% replacement of Rubber shows better results.